2021
DOI: 10.1002/asia.202100469
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Photocatalytic Hybrid Material Composed of Metal‐Organic Cages and TiO2 for Efficient Visible‐Light‐Driven Hydrogen Evolution

Abstract: The design of photochemical molecular devices (PMDs) for photocatalytic H2 production from water is a meaningful but challenging subject currently. Herein, a Pd2L4 type metal‐organic cage (denoted as MOC‐Q2) is designed as a PMD, which consists of two catalytic centers (Pd2+) and four photosensitive ligands (L‐2) with four pyridine anchoring groups. Subsequently, the MOC‐Q2 is combined with TiO2 to form TiO2‐MOC‐Q2 hybrid materials with different MOC‐Q2 contents by a facile sol‐gel method, which have micro/mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 43 publications
8
11
0
Order By: Relevance
“…To investigate the interaction between MOC-PC6 and TiO 2 , X-ray photoelectron spectroscopy (XPS) spectra were obtained (Figure S14). The results indicated that the N 1s peak was located at 399.8 eV for the MOC-PC6 sample, while for the MOC-PC6-TiO 2 sample, the N 1s peak shifted to 402.6 eV, indicating that the MOC-PC6 cages were combined with the surrounding TiO 2 through N–Ti bonding, consistent with our reported literature. , …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…To investigate the interaction between MOC-PC6 and TiO 2 , X-ray photoelectron spectroscopy (XPS) spectra were obtained (Figure S14). The results indicated that the N 1s peak was located at 399.8 eV for the MOC-PC6 sample, while for the MOC-PC6-TiO 2 sample, the N 1s peak shifted to 402.6 eV, indicating that the MOC-PC6 cages were combined with the surrounding TiO 2 through N–Ti bonding, consistent with our reported literature. , …”
Section: Resultssupporting
confidence: 91%
“…The results indicated that the N 1s peak was located at 399.8 eV for the MOC-PC6 sample, while for the MOC-PC6-TiO 2 sample, the N 1s peak shifted to 402.6 eV, indicating that the MOC-PC6 cages were combined with the surrounding TiO 2 through N−Ti bonding, consistent with our reported literature. 46,47 To prove the thermodynamic feasibility to perform visiblelight-driven H 2 evolution from water using the SPMD system, the redox properties of MOC-PC6 and FL were analyzed by cyclic voltammetry (CV) and combined with corresponding optical data. The excitation and oxidation potentials of MOC-PC6, which corresponded to its lowest unoccupied molecular orbital (LUMO) and highest occupied molecular orbital (HOMO) levels, were estimated to be −0.88 and 2.13 V vs normal hydrogen electrode (NHE) on the basis of the CV curves of MOC-PC6 (Figure S15A), ferrocene (Figure S15B), and the intersection of its fluorescence and UV−vis absorption spectra (Figure S15C), respectively, while those of FL were reported as −1.03 and 1.31 V vs NHE with its transition energy (E 0−0 ) value of 2.34 eV in the literature, 30 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The solution of Pd(BF 4 ) 2 (MeCN) 4 (44 mg, 0.1 mmol, 1 eq) in DMF (1 mL) was added into a stirring solution of L-2 (144 mg, 0.2 mmol, 2 eq) in DMF (2 mL), and the resulting solution was stirred at room temperature for 10 min and filtered. Then, the product was precipitated by adding diethyl ether, and it was washed with ethyl acetate and dried in a vacuum to give 118 mg MOC-Q2 as a brown solid (yield: 63%), which was in accordance with our previous work [ 32 ].…”
Section: Methodssupporting
confidence: 85%
“…The synthesis of MOC-Q2 and the preparation of hybrid materials g-C 3 N 4 /MOC-Q2 and Pd/g-C 3 N 4 /L-2 are given in the Experimental Section. The successful formation and the geometric configuration of MOC-Q2 was confirmed in our previous study [ 32 ]. The actual MOC-Q2 contents of the prepared samples g-C 3 N 4 /MOC-Q2 confirmed by ICP-AES are listed in Table S1 .…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation